Crossing symmetry and the crossing map - Correa da Silva, Ricardo; Giorgetti, Luca; Lechner, Gandalf (Reviews in Mathematical Physics, 2024)
We introduce and study the crossing map, a closed linear map of order four acting on operators on the tensor square of a given Hilbert space inspired by the crossing property of quantum field theory. This map turns out to be closely connected to Tomita-Takesaki modular theory; in particular its fixed points define endomorphisms of standard subspaces. We also explain how the crossing property is related to finite index subfactor planar algebras/Q-systems. In the latter case, the crossing map turns out to be a special case of the (unshaded) subfactor theoretical Fourier transform.<br

Inclusions of Standard Subspaces - Lechner, Gandalf; Correa da Silva, Ricardo (Mini-Workshop on Standard Subspaces in Quantum Field Theory and Representation Theory, 2023)

KMS states on Z2-crossed products and twisted KMS functionals - Correa da Silva, Ricardo; Große, Johannes; Lechner, Gandalf (Annales Henri Poincaré, 2024)
KMS states on Z2-crossed products of unital C∗-algebras A are characterized in terms of KMS states and graded KMS functionals of A. These functionals are shown to describe the extensions of KMS states ω on A to the crossed product A⋊Z2 and can also be characterized by the twisted center of the von Neumann algebra generated by the GNS representation corresponding to ω. As a particular class of examples, KMS states on Z2-crossed products of CAR algebras with dynamics and grading given by Bogoliubov automorphisms are analysed in detail. In this case, one or two extremal KMS states are found depending on a Gibbs type condition involving the odd part of the absolute value of the Hamiltonian. As an application in mathematical physics, the extended field algebra of the Ising QFT is shown to be a Z2-crossed product of a CAR algebra which has a unique KMS stat

Lecture Notes on Noncommutative Lp-Spaces - Correa da Silva, Ricardo (2018)
These lecture notes were written during a mini-course on noncommutative Lp-spaces at the Basque Center of Applied Mathematics. It starts presenting the theory of weights and traces in von Neumann algebra, followed by the theory of noncommutative measure. After that, it presents a construction of these spaces in all detail and give some important results e.g. the noncommutative Radon-Nikodym theorem. <br

Modular Structure and Inclusions of Twisted Araki-Woods Algebras - Correa da Silva, Ricardo; Lechner, Gandalf (Communications in Mathematical Physics, 2023)
In the general setting of twisted second quantization (including Bose/Fermi second quantization, S-symmetric Fock spaces, and full Fock spaces from free probability as special cases), von Neumann algebras on twisted Fock spaces are analyzed. These twisted Araki-Woods algebras L_T(H) depend on the twist operator T and a standard subspace H in the one-particle space. Under a compatibility assumption on T and H, it is proven that the Fock vacuum is cyclic and separating for L_T(H) if and only if T satisfies a standard subspace version of crossing symmetry and the Yang-Baxter equation (braid equation). In this case, the Tomita-Takesaki modular data are explicitly determined. Inclusions L_T(K)L_T(H) of twisted Araki-Woods algebras are analyzed in two cases: If the inclusion is half-sided modular and the twist satisfies a norm bound, it is shown to be singular. If the inclusion of underlying standard subspaces KH satisfies an L^2-nuclearity condition, L_T(K)L_T(H) has type III relative commutant for suitable twists T. Applications of these results to localization of observables in algebraic quantum field theory are discussed. <br

Noncommutative Lp-Spaces and Perturbations of KMS States - Correa da Silva, Ricardo (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2018)
We extend the theory of perturbations of KMS states to some class of unbounded perturbations using noncommutative Lp-spaces. We also prove certain stability of the domain of the Modular Operator associated to a p-continuous state. This allows us to define an analytic multiple-time KMS condition and to obtain its analyticity together with some bounds to its norm. The main results are Theorem 5.1.15, Theorem 5.1.16 and Corollary 5.1.18. Apart from that, this work contains a detailed review, with minor contributions due to the author, starting with the description of C*-algebras and von Neumann algebras followed by weights and representations, a whole chapter is devoted to the study of KMS states and its physical interpretation as the states of thermal equilibrium, then the Tomita-Takesaki Modular Theory is presented, furthermore, we study analytical properties of the modular operator automorphism group, positive cones and bounded perturbations of states, and finally we start presenting multiple versions of noncommutative Lp-spaces.<br
Keywords: non-commutative Lp-spaces; KMS states; unbounded perturbations

Operadores p-compactos e a propriedade de p-aproximação - Correa da Silva, Ricardo (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2015)
The purpose of this work is the study of p-compact operators and the p-approximation property. These concepts are connected with important results by A. Gröthendieck about compactness and approximation property that were generalized in [21] and studied in [3], [6] and [7].

p-compact operators and the p-approximation property - Correa da Silva, Ricardo; Lourenço, Mary Lilian (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2014)
The purpose of this work is the study of p-compact operators and the p-approximation property. These concepts are connected with important results by A. Gröthendieck about compactness and approximation property that were generalized in [21] and studied in [3], [6] and [7].<br
Keywords: approximation property; p-approximation property; p-compact operators

Perturbations of KMS states and noncommutative Lp-spaces - Correa da Silva, Ricardo (Journal of Mathematical Physics, 2019)
We extend the theory of perturbations of KMS states to a class of unbounded perturbations using noncommutative Lp-spaces. We also prove certain stability of the domain of the modular operator associated with a ∥·∥p-continuous state. This allows us to define an analytic multiple-time KMS condition and to obtain its analyticity together with some bounds to its norm.

Pure and Mixed States - Alves Barata, João Carlos; Brum, Marcos; Chabu, Victor; Correa da Silva, Ricardo (Brazilian Journal of Physics, 2021)
We present a review on the notion of pure states and mixtures as mathematical concepts that apply for both classical and quantum physical theories, as well as for any other theory depending on statistical description. Here, states will be presented as expectation values on suitable algebras of observables, in a manner intended for the non-specialist reader; accordingly, basic literature on the subject will be provided. Examples will be exposed together with a discussion on their meanings and implications. An example will be shown where a pure quantum state converges to a classical mixture of particles as Planck’s constant tends to 0.<br
Keywords: Quantum states; Classical states; Algebraic QFT; Semiclassical limit

The Dual Dynamical Foundation of Orthodox Quantum Mechanics - Taschetto, Diana; Correa da Silva, Ricardo (Studies in History and Philosophy of Science, 2025)
This paper combines mathematical, philosophical, and historical analyses in a comprehensive investigation of the dynamical foundations of the formalism of orthodox quantum mechanics. The results obtained include: (i) A deduction of the canonical commutation relations (CCR) from the tenets of Matrix Mechanics; (ii) A discussion of the meaning of Schrödinger's first derivation of the wave equation that not only improves on Joas and Lehner's 2009 investigation on the subject, but also demonstrates that the CCR follow of necessity from Schrödinger's first derivation of the wave equation, thus correcting the common misconception that the CCR were only posited by Schrödinger to pursue equivalence with Matrix Mechanics; (iii) A discussion of the mathematical facts and requirements involved in the equivalence of Matrix and Wave Mechanics that improves on F. A. Muller's classical treatment of the subject; (iv) A proof that the equivalence of Matrix and Wave Mechanics is necessitated by the formal requirements of a dual action functional from which both the dynamical postulates of orthodox quantum mechanics, von Neumann's process 1 and process 2, follow; (v) A critical assessment, based on (iii) and (iv), of von Neumann's construction of unified quantum mechanics over Hilbert space. Point (iv) is our main result. It brings to the open the important, but hitherto ignored, fact that orthodox quantum mechanics is no exception to the golden rule of physics that the dynamics of a physical theory must follow from the action functional. If orthodox quantum mechanics, based as it is on the assumption of the equivalence of Matrix and Wave Mechanics, has this “peculiar dual dynamics,” as von Neumann called it, then this is so because by assuming the equivalence one has been assuming a peculiar dual action.
CRIS-Team Scopus Importer:2025-02-17
Keywords: Canonical commutation relations; Discontinuity; Dual action; Dynamical duality; Equivalence of matrix and wave mechanics; von Neumann's process 1 and process 2